Thought and Incarnation in Hegel - Theron, Stephen (Cambridge Scholars Publisher, 2020)
""God became man that man might become God"". This thought, expressed in terms of a sharing of natures, human and divine, is to be found in the most ancient Christian liturgies and still in use, at the Offertory typically. This book shows how Hegel fleshes this thought out, shorn though of picture-language, in conscious or less-than-conscious continuity with this Biblical belief in ""the power to become the sons of God"". This involves some stripping away of the false fleshliness cast over Hegel's ""philosophy of spirit"" by interpreters ignorant of and hence unable to see this element in him,